Linguistic-philological Study of Khachatur Abovyan’s Heritage Written in Ancient Armenian - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2024)
The literary and pedagogical activity of Khachatur Abovyan is closely connected with the history of the formation and development of the new Eastern Armenian literary language. Abovyan, awarded the title of "Great Enlightener", made solid efforts to make education accessible to all children from different layers of society. At that time, the Ancient Literary Armenian language - Grabar, had already lost its communicative capabilities, but the New Literary language - Ashkharabar, had not yet been formed; different layers of society communicated in numerous dialects of the Armenian language. The enlightened image of Mkhitar Abbot and all the activities of the Mkhitarist Congregation inspired the young Abovyan to try to revive the Ancient Literary Armenian language. That is why the great writer created a rich literary and scientific heritage written in the Ancient Armenian language. He wrote spiritual poems in Ancient Armenian, prayers for children and adults, as well as diaries telling about the most important period of his studies in Dorpat. The language of the «Dorpat Diaries» is clear, simple, folk Grabar, in which, in our opinion, young students of Etchmiadzin communicated. Thanks to this research, we have identified the approaches and ideology of the formation of the new literary language of Abovyan, based on the unity of Grabar, dialects and the new literary Armenian language (Ashkharabar).